Increase of serum interleukin 6 and interferon γ is associated with the number of impulses in patients with supraventricular arrhythmias treated with radiofrequency catheter ablation - Pudil, Radek; Vašatová, Martina; Pařízek, Petr; Haman, Luděk; Horáková, Lucie; Palička, Vladimír (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2016)
BACKGROUND: Activation of the immune system plays a pathogenic role in the process of myocardial remodeling in patients with supraventricular arrhythmias. The intensity of this process is associated with the effectiveness of electrical cardioversion and radiofrequency catheter ablation (RFA). The aim of this study was to test the ability of the biochip microarray to detect immune parameters in patients with supraventricular arrhythmias undergoing RFA treatment. METHODS: We used a biochip-based microarray system to determine multiple immune parameters in a group of 35 patients who had undergone RFA for atrioventricular nodal reentry tachycardia (AVNRT), atrial flutter (AFL) and atrial fibrillation (AF). RESULTS: Before the procedure, serum IL-6 and VEGF levels were significantly increased in patients with atrial fibrillation compared to patients with AVNRT (IL-6: 6.4±6.3 ng/L vs. 1.5±0.7 ng/L, P < 0.01; VEGF: 132.4±74 ng/L vs. 88.5±56.4 ng/L, P < 0.01). After the procedure, serum IL-6, VEGF, IFN-γ and MCP-1 levels significantly increased compared to baseline (IL-6: 5.2±4.8 ng/L vs. 2.9±2.1 ng/L, P < 0.01; VEGF: 195.8±160 ng/L vs. 119.8± 110 ng/L, P < 0.05; IFN-γ: 3.1±1.2 ng/L vs. 2.3±0.6 ng/L, P < 0.05; MCP-1: 104.1±84.5 ng/L vs. 54.5±50 ng/L, P < 0.05). Serum IL-6 and IFN-γ were associated with the number of RFA applications (IL-6: r = 0.56, n 33; IFN-γ: r = 0.47, n 33). CONCLUSIONS: This study showed that biochip-based microarray can be useful in the detection of immune activation in patients with arrhythmias and can detect myocardial injury after RF procedures.
Keywords: dospělí; Female; biologické markery; Interferon-gamma; Biomarkers; Adult; mladý dospělý; ženské pohlaví; vaskulární endoteliální růstový faktor A; Catheter Ablation; lidé; Vascular Endothelial Growth Factor A; katetrizační ablace; studie případů a kontrol; Interleukin-6; interferon gama; atrioventrikulární nodální reentry tachykardie; epidermální růstový faktor; Male; mikročipová analýza; Case-Control Studies; Young Adult; interleukin-6; Tachycardia, Atrioventricular Nodal Reentry; Microarray Analysis; lidé středního věku; mužské pohlaví; Epidermal Growth Factor; Middle Aged; Humans